2013
DOI: 10.3340/jkns.2013.54.3.261
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Survival Case of a Primary Malignant Intracerebral Nerve Sheath Tumor

Abstract: We report a long-term survival case of a primary malignant intracerebral nerve sheath tumor (MINST) occurring in the right frontal lobe of a 13-year old boy. After the gross total resection (GTR), we have performed radiation therapy but it recurred 50 months after the surgery, so the second GTR was performed. Later, second tumor recurrence was found 4 months after the second surgery. Subsequently the third GTR, radiotherapy, and chemotherapy were carried out. At present, the patient has been remaining alive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“… 23 In terms of adjuvant therapy, radiotherapy remains the most favored approach; Lee et al found 60 Gy in 30 fractions beneficial in cases of recurrence. 22 Alternatively, different lines of chemotherapy have been suggested by different authors, including combination vincristine, carboplatin, etoposide, single-agent temozolomide, and ifosfamide-based treatment; 3 from our institutional experience, combination procarbazine, lomustine, and vincristine or single-agent lomustine may also be options worth considering. However, the outcome is still poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 In terms of adjuvant therapy, radiotherapy remains the most favored approach; Lee et al found 60 Gy in 30 fractions beneficial in cases of recurrence. 22 Alternatively, different lines of chemotherapy have been suggested by different authors, including combination vincristine, carboplatin, etoposide, single-agent temozolomide, and ifosfamide-based treatment; 3 from our institutional experience, combination procarbazine, lomustine, and vincristine or single-agent lomustine may also be options worth considering. However, the outcome is still poor.…”
Section: Discussionmentioning
confidence: 99%
“…20 Important diagnostic markers include the S100 protein, useful to demarcate nerve sheath tumors from tertiary soft tissue neoplasms; loss of nuclear H3K27me3 expression, seen in most MPNSTs; 7,21 negative glial fibrillary acidic protein (GFAP) expression, which helps exclude desmoplastic astrocytoma, gliofibroma, and gliosarcoma; and negative synaptophysin and neurofilament protein, which reliably distinguish MINSTs from desmoplastic ganglioglioma. 22 Other differential diagnoses include other tumors such as rhabdomyosarcoma, gastrointestinal stromal tumor, and meningioma. 20 In our case, S100 positivity coexisting with patchy GFAP expression proved challenging and certainly delayed diagnosis.…”
Section: Diagnosismentioning
confidence: 99%